PENINGKATAN KUALITAS BENIH KENTANG DI SUMATERA BARAT: INVESTIGASI TERMOTERAPI UNTUK ELIMINASI VIRUS PADA TUNAS KENTANG CINGKARIANG - Silvia Permata Sari; Suliansyah, Irfan; Kusumawati, Aries; Evricia, Oliviana (Jurnal Pertanian Agros, 2025)
Cingkariang potato is a superior local variety from West Sumatra, yet its productivity is often hindered by poor seed quality due to viral infections. This study evaluated the effectiveness of thermotherapy in eliminating viruses from Cingkariang potato shoots. The research design used factorial RAL with two factors, namely thermotherapy temperature (30°C and 35°C) and duration (5, 10, 15, and 20 days). Results showed that temperature significantly affected the number and height of shoots, while duration influenced shoot emergence. In virus infection tests, 30°C successfully eliminated PVX but not PVY, whereas 35°C eliminated both viruses, as indicated by the absence of morphological symptoms in indicator plants. Duration had no significant effect on virus elimination efficacy. This study recommends 35°C as the optimal thermotherapy protocol to improve Cingkariang potato seed quality.